Trends of incidence, mortality, and disability-adjusted life years of oral cancer in Latin America - Brenda Yuliana Herrera Serna; Julián Andrés Orozco Betancourt; Olga Patricia López Soto; Regiane Cristina do Amaral; María del Pilar Cerezo Correa (Associação Brasileira de Pós-Graduação em Saúde Coletiva, 2022)
ABSTRACT Objective: To describe the trend in incidence, mortality and Disability Adjusted Life Years of oral cancer in Latin America according to sex between 2000 and 2020. Methods: This ecological study extracted oral cancer information from 20 Latin American countries from the GBD-2020 database. Oral cancer burden was described by age-standardized rate (ASR) of incidence, mortality, and DALYs. The data was compared according to sex and countries. Trends (Average Annual Percentage Change-AAPC) were estimated for each indicator, sex, and country between 2000 and 2020 using Joint-point software. Results: Between 2000 and 2020, the highest incidence of oral cancer (ASR) occurred in Cuba (5.18), Brazil (4.38) and Uruguay (4.62). The countries with the highest mortality for both sexes were (ASR): Cuba (2.89), Brazil (2.71) and the Dominican Republic (2.58). The DALYs registered an average of 37.52 (Women: 22.39; Men: 52.62). The Dominican Republic reports increasing trends in incidence (AAPC: Men: 2.2; Women: 1.4), in mortality (AAPC: Men: 1.8; Women: 1.1), and in DALYs (AAPC: Men: 1.0; Women: 2.0). Costa Rica shows decreasing trends in men in incidence (AAPC: −1.3), mortality (AAPC: −1.6), and DALYs (AAPC: −1.8). Conclusion: Oral cancer shows increasing trends in: the incidence in both sexes in 10 countries, in mortality and DALYs in 6 countries, while the affectation between sexes does not show differences in trends.